Cord blood spot thyroid stimulating hormone for screening of congenital hypothyroidism - E., Narayanan; Seeralar, Arasar (International Journal of Contemporary Pediatrics, 2020)
Background: Congenital hypothyroidism is one of the most common causes of mental retardation in pediatric age group. Screening for congenital hypothyroidism is one of most cost effective tools to prevent mental retardation among the general population. Umblical cord TSH estimation remains an easily available option for screening of congenital hypothyroidism. Aims and objectives was to estimate correlation between TSH obtained from cord blood TSH and heel prick TSH at 3rd day of life using blood spot. To estimate the predictability to rule out congenital hypothyroidism using cord blood spot TSH and to determine whether cord blood TSH can be advocated to screen congenital hypothyroidism. Methods: Prospective study conducted in department of Neonatology, IOG, Egmore after obtaining consent from parents. The study was carried out in two phases. First phase, to establish correlation between cord blood spot TSH and heel prick TSH and to establish median cutoff point of TSH .Second phase, to establish cord blood spot TSH as screening method. Results: The birth weights ranged between 2.5 to 4.3 kg. TSH values ranged from 2.0-33.3mlU/L. The mean value was 16.45mlU/L. A cutoff value of 20mlU/L was used for recall testing of complete thyroid profile (T3, T4 and TSH). Thirty six infants were recalled for repeating complete thyroid profile. Conclusions: Congenital hypothyroidism (CH) is the one of the most common preventable causes of mental retardation which can be detected by measuring cord blood TSH .Cord blood TSH can be advocated in national public health program as a routine so that all babies can be tested before discharge thereby minimising interventions for the baby.